Giraffes - Marsh, Laura F.; National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2016)
Discusses the facts, habits and behaviors of giraffes.
Beginning readers will get information about giraffes, including their diet, life cycle, physical characteristics, behaviors, and habitat.
Guess who! -- Big bodies -- Giraffes at home -- Mealtime -- 6 fun facts about giraffes -- Big babies -- On the lookout -- Naptime -- What in the world?
OSLIS\Gale Nat Geo eBooks(2/2/23).
Ages 4-6.
Description based on print version record.
Keywords: Giraffe -- Juvenile literature; Giraffe; Giraffe -- Juvenile literature; Giraffe; JUVENILE NONFICTION / Animals / Giraffes; JUVENILE NONFICTION / Reader - Beginner; JUVENILE NONFICTION / Science & Nature / Zoology; Electronic books- OSLIS; Readers (Publications); Juvenile works; Readers (Publications); Electronic books